2021
DOI: 10.13057/nusbiosci/n130204
|View full text |Cite
|
Sign up to set email alerts
|

Ant diversity inhabited oil palm plantations in a peatland in Sumatra, Indonesia

Abstract: Abstract. Johari A, Hermanto MA, Wulandari T. 2021. Ant diversity inhabited oil palm plantations in a peatland in Sumatra, Indonesia. Nusantara Bioscience 13: 158-163. Ant community is one of the soil biotic components with diverse roles, including pollinators, predators, decomposers, parasites, and herbivores. Changes in land use from natural habitats to plantations affect the diversity and composition of ants because these groups are very vulnerable to environmental changes. The purpose of the study was to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Lichtenstein et al [16] explained that the presence of predators and the abundance of predators are influenced by the presence of prey and the behavior of the prey. The results of a study by Johari et al [17] which explored the diversity of ant species in peatlands, also did not find M. castanea ants in oil palm plantations on the peatlands they explored, as well as the results of research by Yanarita et al [18] which only found obtained 2 types of ant species, namely Solenopsis invicta and Monomorium minimum in the peatland of the Jelutong forest, Central Kalimantan. Peatland often has special characteristics such as high acidity and low water content.…”
Section: Resultsmentioning
confidence: 91%
“…Lichtenstein et al [16] explained that the presence of predators and the abundance of predators are influenced by the presence of prey and the behavior of the prey. The results of a study by Johari et al [17] which explored the diversity of ant species in peatlands, also did not find M. castanea ants in oil palm plantations on the peatlands they explored, as well as the results of research by Yanarita et al [18] which only found obtained 2 types of ant species, namely Solenopsis invicta and Monomorium minimum in the peatland of the Jelutong forest, Central Kalimantan. Peatland often has special characteristics such as high acidity and low water content.…”
Section: Resultsmentioning
confidence: 91%
“…assumed that influenced by the presence of cocoa leaf litter at the insect sample collection area. Johari et al (2021) stated that Anoplolepis sp. is one of the most common ant species found in an oil palm plantation because litter is still found in the location that allows Anoplolepis sp.…”
Section: Abundance and Species Richness Of Insectmentioning
confidence: 99%